SCRUTINY ON PHYSICAL PROPERTIES OF SAWDUST FROM TROPICAL COMMERCIAL WOOD SPECIES: EFFECTS OF DIFFERENT MILLS AND SAWDUST’S PARTICLE SIZE - Rizki Maharani; Tamai Yutaka; Takashi Yajima; Terazawa Minoru (Indonesian Journal of Forestry Research, 2010)
Physical properties of sawdust (i.e. particle size distribution, particle density, porosity, and water retention) from five tropical commercial wood species (Shorealeprosula, Dryobalanops lanceolata, Dipterocarpus cornutus, Shorea laevis, and Eusideroxylon zwageri)  as prepared in various mill types (i.e. handsaw, sawmill, and milling ) were analyzed. This study aims to look into the relationship and interconnected between the use of different mill types, density of wood species origin and physical properties of the resulting sawdust. Generally, different mill types produced sawdust with different particle size distributions. The use of a handsaw produced a higher proportion of oversized particles (OS) and coarser particle size (CPS) than that of sawmill and milling , while also commonly producing the lowest proportion of fine particle size (FPS). For each wood species, the proportion of OS was lower than that of CPS and FPS. In addition, particle density and water retention produced by handsaw in CPS as well as FPS was the smallest, followed in an increasing order sawmill and milling. Porosity of CPS and FPS was the highest in handsaw-cut sawdust, followed in a decreasing order sawmill and milling cut sawdust. This study showed that the different mill types and particle size influenced the physical properties of sawdust. Further, analysis of influential factors on porosity and water retention using General Linear Model revealed that particle density inflicted a strong influence on porosity, as did particle size on water retention.